When home is not safe: writings on domestic verbal, emotional and physical abuse - Skillman, Judith; Lucas, Linera (Exposit, 2021)
I. Home -- Weather ; Drafting a Flight Plan / Heidi Seaborn -- Hit Me / Jennifer Jenkins -- The Ballet / Susan April -- Anger Is an Arrow ; Stick Figure Family ; The Secret Goldfish / Howie Good -- What's True of the Garden Pea / Emma Brousseau -- Fissure / Wren Tuatha -- Balcony, 3 a.m. / Chelsea Clammer -- Her Father's Daughter / Nina Fosati -- holy/days / RK Taylor -- You Smiled ; Michael / Lynn Magill -- Words 'Too Dark' for the Father's Day Edition / Cynthia Steele -- Packs ; Drowned ; The Best of a Bad Year / Kurt Olsson -- Ever Closer / J. Flynn Doncaster -- II.Trauma -- Abroad / Lindsay Erdman -- Kintsugi / LeeAnn Olivier -- Girl in Rape Kit / Aimee Parkison -- A Slice of Summer / Victoria Elizabeth Ruwi -- Wine Song ; How to Survive Abuse ; A Steady Whip / Mary Ellen Talley -- Voices from the Streets / Ogu Chukwuebuka Kizito -- Mandamientos: Lover to Beloved ; I Forgive / Carolyne Wright -- Kitchen Table / Paul Rousseau -- It wasn't the first time he hit me / Jonaki -- Reading the Lines / Darlene Goetzman -- From Where I Live Now / Anne Spollen -- Why Are They Fighting? / Izzy Wilson -- When His Words Became a Drug / Christina Hoag -- The Fixer / Toni Felella -- Beginnings / Sally Quon -- His face right in my face; The Weight of Words in Our Hands Like Water ; This is what happened / Gayelene Carbis -- A Game of Cat and Mouse / Kelsey Brown -- Excerpt--The Queen in the Mirror / Polly Buckingham -- III. PTSD -- Pine / Tina Barry -- Counting Raindrops / Roxanne James -- Pearls Before Swine / Lillo Way -- Stone Lies / Sally Showalter -- Fire Line / H.M. Clark -- i keep secrets stashed in a lock box ; Abandoned Doll ; cold sheets ; secrets stashed in tiny orange pill bottles / Danielle Hark -- Memoir Excerpts ; Memoir Excerpts II / Lexy Courneya -- The Out of Body Girl / Joyce Hayden -- Eiffel Tower ; On a Hot Summer Night for Revenge ; The Truth of Lies, The Lies of Truth ; Sharp / Marjorie Maddox -- IV. In Retrospect -- The Woman Who Held Her Tongue / Susan Landgraf -- House of Cards ; A Picnic / Carol Smallwood -- Two-Year Slide in Brooklyn Heights / Rosanne Ehrlich -- Saddle Up ; Signal / Linera Lucas -- Weaving Rope / Lindsey Heatherly -- My First Online Love / Robert Kingett -- Tug of War / Alice Ting Liu -- Trellis ; Years Later / Judith Skillman -- Lost in Transmission / Jeff Burd -- Last Supper / Mary Zelinka -- Red Flag / Sailor Holladay -- Heretic / Alison Stone -- Pushed Out of the Chevy, She Adjusts Her Miniskirt / Tina Kelley -- Twenty Years of Rain / Meggie Royer.